STATUS KUALITAS AIR DI KAWASAN PARIWISATA NUSA PENIDA - Nyoman Sudipa; Made Sudiana Mahendra; Wayan Sandi Adnyana; Ida Bagus Pujaastawa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2020)
Environmental water quality is very influential on environmental sustainability and tourism in the Nusa Penida Tourism Area. Changes in environmental water quality are influenced by human activities in utilizing environmental resources. As a developing tourism area, Nusa Penida has a source of environmental water from springs, groundwater and has marine waters with biodiversity that become underwater paradise. The method used by analyzing water quality uses a standardized quality approach based on Bali Governor's Regulation No. 16 of 2016 concerning Environmental Quality Standards and Environmental Damage Quality Criteria and to find out the water pollution index using the approach of the Decree of the Minister of Environment No. 51 of 2004, then compared with environmental water quality using environmental water quality tests that have been carried out in the Study of Analysis Regarding the Environmental Impact of the Nusa Penida Tourism Area in 1998.Tests for the quality of sea water, well water and spring water in 2019 each showed relatively better results compared to the results of quality tests for sea water, well water and spring water in 1998. Influential parameters The index of sea water pollution, well water and spring water in Nusa Penida are turbidity parameters, free ammonia (NH3-N) dissolved residue (TDS) and total coliform, respectively.Keywords: environment; quality; water; tourism; Nusa Penida.